CHARACTERIZE ON THE HEISENBERG GROUP WITH LEFT INVARIANT LORENTZIAN METRIC - Turhan, Essin; Korpinar, Talat (De Gruyter Poland Sp Z O O, 2009)
In this paper, we consider the biharmonicity conditions for maps between Riemannian manifolds and we characterize non-geodesic biharmonic curve in Heisenberg group H-3 which is endowed with left invariant Lorentzian metric.
Keywords: Heisenberg group; Lorentz metric; geodesic